Rethinking new strategies of river management and sustainability in the Inanam-Likas river basin, Kota Kinabalu, Sabah (Malaysia) - Eko Prayitno Joko; Adi Jafar; Ramli Dollah; Marsitah Mohd Radzi (Abdullah Kuzu, 2021)
In the last two decades we have witnessed the problem of river pollution becoming a discourse among social and humanitarian scientists. These developments have seen the emergence of various approaches in trying to solve the problems. However, until now the problems that plagued the world have not been resolved, while millions of dollars have been spent with hundreds of thinkers have been included, no success results have been shown. That is why this paper argues that the discourse related to river sustainability needs to go against the flow (reverse) by making changes of thought as the mainstay to realise it. Using Braudel's approach to the concept of time and space, the author argues that the archipelago's maritime paradigm needs to be redeveloped as a "space" that has long been marginalised to be restored to its proper place like the heyday of maritime civilisation. The expansion of this maritime paradigm allows the community to view the river as a "space" that needs to be preserved due to the function that the river plays in human life which has never changed. At the same time, the author also argues that with the development of the maritime paradigm allows the role of coastal communities to be included in carrying out their responsibilities as agents of change which has long been nominated as a causative factor of river pollution. Furthermore, the role will be complemented by the presence of the authorities as the driving force in ensuring that the problem of river pollution can be solved through enforcement. Even so, the author argues that the authorities need to change the mentality of those who have long considered the coastal community to be "enemies" to "friends", thus the presence of the community along the river board is an "asset" rather than a burden. The relevance of this difficult "three-layer" role is presented by the author so that the goal of preserving the Inanam-Likas river basin can be realised as much as possible.